SITUATIONAL LEADERSHIP, KNOWLEDGE SHARING, WORK STRESS ON EMPLOYEE PERFORMANCE AND THEIR IMPACT ON EMPLOYEE PERFORMANCE - Andrea Devani Sekareza; Endang Sulistiyani; Inayah Inayah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
PT Eastwind Mandiri Cangkiran is a manufacturing company that produces and exports furniture from forest products. This study aims to empirically examine the effect of situational leadership, knowledge sharing, and job stress on employee performance at PT Eastwind Mandiri Cangkiran. Data was collected by interview, observation, literature study, and distributing questionnaires. The sampling method used the census model, namely the entire population of 60 respondent data. The data analysis technique was carried out by multiple linear regression analysis. The results of the analysis show that situational leadership, knowledge sharing, and job stress have a significant positive effect on employee performance. Knowledge sharing variable has a dominant impact in improving employee performance. Keywords: situational leadership, knowledge sharing; job stress; employee performance